Onset of fast ice flow in Recovery Ice Stream, East Antarctica: a comparison of potential causes. Issue 223 (2014) - Langley, K.; Tinto, K.; Block, A.; Bell, R.; Kohler, J.; Scambos, T.
Abstract: Recovery Ice Stream has multiple branches reaching far into the East Antarctic ice sheet. We use new airborne and ground-based geophysics to give the first comprehensive overview of the upper catchment and, by constraining the physical setting, to advance our understanding of the controlling mechanisms for the onset of fast flow. The 400 km wide ice stream extends towards the Recovery Subglacial Lakes, a region characterized by a crustal boundary, a change in bed roughness, a bedrock topographic step and four topographic basins (A–D), three of which (A–C) contain subglacial water. All these characteristics are considered potential causal mechanisms that contribute to the onset of fast flow. In Lakes B and C the subglacial water is located in basins with sharp downstream ridges, in contrast to the gently sloping ridge on the downstream margin of Lake A. The fastest-flowing branch of the ice stream emanates from Lake A. The presence of multiple causal mechanisms along the four Recovery Lakes allows us to identify basal water as a dominant factor for the onset of fast flow, but only if it is stored in a shallow-sided basin where it can lubricate the flow downstream. Relatively minor topographic barriers appear to inhibit streaming.